2018
DOI: 10.14260/jemds/2018/1082
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of Breast- A Study Profile

Abstract: BACKGROUND Breast cancer is the most common site-specific cancer in women and is the leading cause of death from cancer for women of age 40 to 44 years. It is the second most common cancer in Indian women next only to carcinoma cervix. It is one of the commonest causes of death in many developed countries and becoming frequent in developing countries as well. Aims and Objectives of Study-1. To study the clinical presentations and epidemiological factors of patients with carcinoma breast in rural setup. 2. To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…These included following lesions-UDH, ADH, and DCIS. Similar related studies were reported [14][15][16][17]. Studies reported by Yeola et al [18,19] Anand et al [20] were reviewed.…”
Section: Discussionsupporting
confidence: 66%
“…These included following lesions-UDH, ADH, and DCIS. Similar related studies were reported [14][15][16][17]. Studies reported by Yeola et al [18,19] Anand et al [20] were reviewed.…”
Section: Discussionsupporting
confidence: 66%
“…Chemotherapy (dacarbazine, temozolomide, cisplatin and taxol) is mostly used for pre and postoperative adjuvant-therapy [16][17][18][19][20]. Studies related to carcinoma of breast and lungs have been reported [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the existing studies are conflicting in their results. Some studies suggested that Sr. LDH was associated with poor prognosis in breast cancer, [7,8,9] whereas other studies have faild to demonstrate such correlations.…”
Section: Introductionmentioning
confidence: 99%